2018
DOI: 10.1186/s40623-018-0780-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced ionizing radiation on the cloud electricity after the Fukushima nuclear accident

Abstract: The vertical downward component of the DC atmospheric electric field, or potential gradient (PG), at Kakioka 150 km southwest of the Fukushima Dai-ichi Nuclear Power Plant (FNPP1) was analyzed before and after the FNPP1 accident to examine possible influence of floating radioactive particles on the PG under the highly electrified clouds. Using 1-min PG data from March 13 to April 30 (late April 2011 corresponding to the time when floating radioactive materials decreased significantly) from 2006 to 2015, time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…During nuclear explosions, nuclear lightning can occur on the electric charge distribution in a strong electric field (Holzer, 1972;Williams et al, 1988). There may be a negative charge at the top of the thundercloud (Holzer, 1972), unlike the proposed model of Yamauchi et al (2018).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…During nuclear explosions, nuclear lightning can occur on the electric charge distribution in a strong electric field (Holzer, 1972;Williams et al, 1988). There may be a negative charge at the top of the thundercloud (Holzer, 1972), unlike the proposed model of Yamauchi et al (2018).…”
Section: Discussionmentioning
confidence: 96%
“…If the air-Earth current measurements were carried out, one would expect bipolar pulses related to the time change in space charge radioactive cloud. The model of the radioactive cloud or aerosol with polarized electric charges (positive at the top, negative at the bottom) was proposed by Yamauchi et al (2018) to analyze spikes in the course of an electric field during the Fukushima accident. During nuclear explosions, nuclear lightning can occur on the electric charge distribution in a strong electric field (Holzer, 1972;Williams et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that the PG at KAK and MMB decreased due to radioactive materials released by nuclear test explosions in the 1950s and 1960s (Kondo, 1959, 1963) (Figure 2). Moreover, it has been found that the PG at KAK was affected by radioactive materials released by the Fukushima Daiichi nuclear power plant accident in 2011 (Takeda et al, 2011; Yamauchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%